A STUDY ON COMPUTER ASSISTED LEGAL RESEARCH: AN INESCAPABLE TREND - DUBEY, RASHMI; SHAIKH, ANISA (International Journal of Psychosocial Rehabilitation, 2020)
“Research: The Distance betweenan Idea and Realization” David Sarnoff This paper focuses on A Study On Computer Assisted Legal Research: An Inescapable Trend. Traditionally, legal research was accomplished manually using a law library, books, periodicals, indexes, and digests. When conducting manual research, manual indexes are used that have been typically written by attorneys, librarians, or experts in indexing. The researcher here is striving to put forward a view that for legal researchers inexperienced in a particular area of the law, manual research providesfeatures that give them insight into doctrine, concepts, and analysis but with the change in time Computer-Assisted Legal Research offers some advantages over Manual legal research.Computer Assisted Legal Research is the technology that allows lawyers, judges, academicians and students to bypass the traditional law library and locate statutes, court cases, and other legal references in minutes using a personal computer, research software or the internet, and an online connection.This paper is emphasizing on the emerging use of technology for legal research purpose as well.